2020
DOI: 10.3390/su12177207
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Analysis of Active Packaging for the Fresh Cut Vegetable Industry by Means of Attributional & Consequential Life Cycle Assessment

Abstract: In order to enlarge the shelf life and avoid the waste of fresh-cut (FC) products, novel packaging techniques with antimicrobial properties have been proposed. In this work, we analyzed the potential environmental benefits of using films reinforced with bactericidal ZnO nanoparticles (NP) for FC produce packaging, when compared to the traditional polypropylene (PP) films. A biodegradable, polylactic acid (PLA) package and a non-biodegradable, polypropylene package, both coated with ZnO NP, were considered as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…These results reinforce the hypothesis that increasing product shelf life through alternative packaging is crucial to reduce food waste, even if the impact of the packaging itself increases (see subsection 3.3.1). Previous studies on other AP alternatives achieve similar results, although the active packaging materials were different, as well as the approach used to estimate the food waste generated (Manfredi et al, 2015;Vigil et al, 2020;Zhang et al, 2015). The method used to estimate the amount of wasted food due to shelf life expiration is thus decisive when comparing the two product-packaging systems.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These results reinforce the hypothesis that increasing product shelf life through alternative packaging is crucial to reduce food waste, even if the impact of the packaging itself increases (see subsection 3.3.1). Previous studies on other AP alternatives achieve similar results, although the active packaging materials were different, as well as the approach used to estimate the food waste generated (Manfredi et al, 2015;Vigil et al, 2020;Zhang et al, 2015). The method used to estimate the amount of wasted food due to shelf life expiration is thus decisive when comparing the two product-packaging systems.…”
Section: Discussionmentioning
confidence: 73%
“…These data allowed the parameters of the three models to be obtained, although the results were not validated with real data. This model was later adopted by Vigil et al (2020) in a case study on fresh cut salad. An economic perspective was adopted by Gutierrez et al (2017) to determine the waste at retailer level in a case study on two packaging alternatives for cheesecake.…”
Section: Review On Shelf Life Of Foods and Related Food Wastementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, current agricultural practices have a great impact on the LCA of biobased products, being sustainable practices needed to reduce eutrophication, prevent soil erosion, and protect biodiversity. Incidentally, an LCA study carried out by Vigil et al [502] on active packaging for the fresh-cut vegetable industry, indicated that agricultural production of fresh lettuces is responsible for most impact factors, followed by packaging manufacturing. An alternative to tackle the latter, the use of fully renewably sourced electricity for packaging molding technology could reduce in over 50% the potential impact [358].…”
Section: Life Cycle Assessment Of Single Use Biobased Compositesmentioning
confidence: 99%
“…23 Outside the biorefining scenario, LCA has been used to analyze the environmental benefits of active packaging for fresh cut vegetables with bactericidal nanoparticles in comparison with traditional antimicrobial techniques. 24 It has also compared the traditional polypropylene plastic film with a biodegradable polylactic acid package. In both cases, LCA profiles presented better results for the biodegradable and traditional packaging with nanoparticles than traditional antimicrobial methods.…”
mentioning
confidence: 99%